Heart rate and dyssynchrony in patients with cardiac resynchronization therapy: a pilot study. (4th May 2017) - Naar, Jan; Mortensen, Lars; Winter, Reidar; Johnson, Jonas; Shahgaldi, Kambiz; Manouras, Aristomenis; Braunschweig, Frieder; Ståhlberg, Marcus
Abstract: Objectives: The objective of this pilot study was to describe the impact of paced heart rate on left ventricular (LV) mechanical dyssynchrony in synchronous compared to dyssynchronous pacing modes in patients with heart failure. Methods: Echocardiography was performed in 14 cardiac resynchronization therapy (CRT) patients at paced heart rates of 70 and 90 bpm in synchronous- (CRT), and dyssynchronous (atrial pacing + wide QRS activation) pacing modes. LV dyssynchrony was quantified using the 12-segment standard deviation model (Ts-SD) derived from Tissue Doppler Imaging. In addition, cardiac cycle intervals were assessed using cardiac state diagrams and stroke volume (SV) and filling pressure were estimated. Results: Ts-SD decreased significantly with CRT at 90 bpm (25 ± 12 ms) compared to 70 bpm (35 ± 15 ms, p  = .01), but remained unchanged with atrial pacing at different paced heart rates ( p  = .96). The paced heart rate dependent reduction in Ts-SD was consistent when Ts-SD was indexed to average Ts and systolic time interval. Cardiac state diagram derived analysis of cardiac cycle intervals demonstrated a significant reduction of the pre-ejection interval and an increase in diastole with CRT compared to atrial pacing. SV was maintained at the higher paced heart rate with CRT pacing but decreased with atrial pacing. Discussion: Due to the small sample size in this pilot study general and firm conclusions are difficult to render. However, the data suggest that pacing at higher heart rates acutely reduces remaining LV dyssynchrony during CRT, but not during atrial pacing with dyssynchronous ventricular activation. These results need confirmation in a larger patient cohort.